PENGARUH PENGAJARAN NILAI MORAL DALAM PEMBELAJARAN PPKN - Suratni Suratni (Center of Language and Cultural Studies, 2014)
This study examines the relationship between value of morality to the civic education for the secondary school students. Chi-Square was used to analyze the data. The findings of the study were revealed that a significant correlation was proven by value of moral (X) to civics education achievement (Y) with the Chi Square coefficient = 46.09 that was greater (>) than -table 9.49 at the significance level 0.05 and df = 4. It meant that the more teaching of value of moral was good, the civics education achievement became more and more raising, too.